MicroRNAs interfere with DNA methylation in rheumatoid arthritis synovial fibroblasts. Issue 2 (14th October 2016) - Gaur, Niharika; Karouzakis, Emmanuel; Glück, Selene; Bagdonas, Edvardas; Jüngel, Astrid; Michel, Beat A; Gay, Renate E; Gay, Steffen; Frank-Bertoncelj, Mojca; Neidhart, Michel
Abstract : Background: The DNA of rheumatoid arthritis synovial fibroblasts (RASF) is globally hypomethylated; this contributes to an aggressive behaviour. In an attempt to remethylate these cells, we supplemented with methyl donors. We investigated the possible interference of microRNAs (miRs). Material and methods: RASF were treated with L-methionine or betaine. Transcripts of de novo methyltransferases (DNMTs) and miRs were measured by real-time PCR, and a transcription PCR array was performed. Levels of homocysteine, matrix metalloproteinase-1 (MMP-1) and global DNA methylation were determined. Transfection with lipofectamine was performed with specific pre-miRs and anti-miRs, such as miR29 and let7f. Results: L-methionine was more efficient to increase DNA methylation than betaine. This was associated with a reduced expression of DNMT3A mRNA in betaine-treated RASF. Betaine increases the expression of miR29 in RASF which targets DNMT3A, thereby limiting the remethylation process. Nevertheless, betaine inhibited the expression of multiple transcription factors, decreased the release of MMP-1, biosynthesis of homocysteine and cell migration. Conclusion: Alterations in cellular miRs profiles, in particular the upregulation of miR29, which targets DNMT3A, may limit the efficiency of betaine if it is used as DNA remethylating agent. However, L-methionine also has similar impact on miR29 expression. On the other hand, betaine has multiple other beneficial effects on the activated phenotype of RASF; it is not excluded that the effect of betaine on DNMT3A is, at least in part, indirect. Clinical trials with betaine could be promising.